2023
DOI: 10.20961/javanologi.v6i1.71564
|View full text |Cite
|
Sign up to set email alerts
|

Local Wisdom in the Serat Menak Lare as Teaching Materials in Secondary Schools (A Study of Literature Anthropology)

Abstract: <p>Local wisdom as part of the cultural values possessed by certain communities is considered as a form of defense of culture against incoming foreign cultures. This study aims to describe (1) the aspects of local wisdom in Serat Menak Lare; (2) the most prominent cultural aspects contained in Serat Menak Lare; (3) the relevance of Serat Menak Lare with Indonesian language learning in senior high school. The research type was descriptive qualitative study with an anthropological literary study approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…This is shown by Timothy Mo, a writer from China, in his novel, which tells about the life of Chinese people in Western countries (Stănescu, 2008). Literary anthropology analyzes a literary work by paying attention to anthropological theory and data (Rahmawan & Tiyasmala, 2023;Ratna, 2009). So, it can be concluded that literary anthropology tries to analyze literary works using cultural science.…”
Section: Introductionmentioning
confidence: 99%
“…This is shown by Timothy Mo, a writer from China, in his novel, which tells about the life of Chinese people in Western countries (Stănescu, 2008). Literary anthropology analyzes a literary work by paying attention to anthropological theory and data (Rahmawan & Tiyasmala, 2023;Ratna, 2009). So, it can be concluded that literary anthropology tries to analyze literary works using cultural science.…”
Section: Introductionmentioning
confidence: 99%